An Analysis Figurative Language in Bruno Mars Selected Song Lyric: “It Will Rain” - Patrisia Adma Renda; Desak Putu Eka Pratiwi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
Language is an important role in human life. Humans need language in order to communicate with other people, interact and also to get information. With the existence of language, every human being can express an idea or ideas, imagination and desires the others. Language serves to unite the relationship between human beings. Language can also be called art because with language, we can express ideas or ideas with literal works commonly used in language arts or commonly called figurative language. Figurative language is a form of parable or not the actual meaning used to write or convey things related to everyday life. This study was conducted to analyze the types of figurative language in Bruno Mars' selected song lyric: "It Will Rain". This study uses the theory proposed by Perrine (1969) and the theory of Knickerbocker and Reninger (1963). the type of figurative language used in the lyrics of Bruno Mars' chosen song: "It Will Rain". Apart from that, the researcher also uses the theory proposed by Leech (1981) which serves to determine the meaning contained in the lyrics of Bruno Mars' chosen song. To collect data , the researcher first looks for the song lyrics from the website, then reads and understands the song lyrics. After the data collection technique, the researcher begins to select, code and classify all data containing figurative language according to the type of figurative language. The researcher analyzed the data using qualitative and descriptive methods. From the results of the study, it shows that there are three categories of types figurative language that can be found in the lyrics of the song are: hyperbole, simile, and repetition. 7 data in this study. There are 4 or 57% hyperbole data, 1 or 14% simile data and 2 or 29% repetition data. From the data obtained, the researcher concludes that hyperbole is the most dominant used in the Bruno Mars' selected song lyrics: "It Will Rain".